Injectable hydrogel adhesive with rapid solidification and anti-swelling properties and application thereof

By using end-biodegradable poloxamer and photoinitiator in injectable hydrogel adhesives, combined with thermally sensitive shrinking nanomicrobes and adhesion functional small molecules, the problems of slow curing speed and water absorption expansion are solved, and the effects of rapid curing and anti-swelling are achieved, suitable for wound sealing and rapid hemostasis.

CN115536833BActive Publication Date: 2025-04-11SHENZHEN INST OF ADVANCED TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202210921559.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-02
Publication Date
2025-04-11
Estimated Expiration
2042-08-02

AI Technical Summary

Technical Problem

Existing injectable hydrogel adhesives have slow curing speed and expanding water absorption volume in a water environment, resulting in a reduced adhesion performance and risk of wound rebleeding.

Method used

The cohesion of the hydrogel is enhanced by end-biodegradation of poloxamer, adhesion functional small molecules, photoinitiators and soluble solutions by rapidly curing and thermally-sensitive shrinking nano micelles under light conditions, providing anti-swelling characteristics and long-lasting tissue adhesion.

Benefits of technology

It achieves rapid and controllable curing, good biosafety and controllable biodegradation speed, and has excellent tissue adhesion and mechanical properties, avoiding compression damage and wound closure failure caused by volume changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115536833B_ABST
    Figure CN115536833B_ABST
Patent Text Reader

Abstract

The invention discloses an injectable hydrogel adhesive and application with both rapid curing and anti-swelling, the injectable hydrogel adhesive comprises the following components by mass percentage: terminal biodegradable poloxamer 5%-20%, adhesion functional small molecule 0.1%-5%, photoinitiator 0.1%-0.5%, dissolved amount of dissolving solution, terminal biodegradable poloxamer is obtained by introducing terminal modification structure into two ends of poloxamer; the molecular weight of the terminal modification structure is less than 300, containing biodegradable ester bond or amide bond, and the end is a carbon-carbon double bond. The injectable hydrogel adhesive has the dual performance of rapid adhesion and anti-swelling, and can achieve adhesion to moist tissue within a few seconds after ultraviolet light irradiation, can be used for wound closure and rapid hemostasis, is particularly suitable for wound treatment of neurosurgery, avoids the risk of postoperative adhesive volume expansion compressing nerve tissue, and ensures the safety of patients after surgery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to an injectable hydrogel adhesive with rapid solidification and anti-swelling properties and an application thereof. Background Art

[0002] When dealing with injuries caused by accidental trauma or surgery, wound closure and rapid hemostasis are necessary, and commonly used methods include sutures, staples or bandages. However, these techniques are not suitable for closing fragile tissues or wounds accompanied by liquid or gas leakage because they will cause secondary damage to the tissue and have unsatisfactory gas or liquid sealing. In recent years, with the development of biomaterials science, researchers have developed a series of injectable hydrogel adhesives for wound closure and wound hemostasis, such as fibrin glue and polymer hydrogels. They are easy to use, cause little damage to soft tissues, have good water tightness and air tightness, and have received widespread attention in clinical treatment.

[0003] There is a problem of slow curing speed in current injectable hydrogel tissue adhesives, and the precursor solution that has not yet formed gel after injection is easily washed away by blood or body fluid, causing leakage and loss, and it is impossible to achieve wound closure and rapid hemostasis, and it is not suitable for closing wounds or hemostasis with continuous liquid outflow. In addition, most of these injectable hydrogel tissue adhesives absorb water in an aqueous environment and volume swelling occurs, which has the risk of causing surrounding tissue compression damage, especially neural tissue (brain and spinal cord). In addition, volume swelling also causes hydrogel tissue adhesive mechanical properties and tissue adhesion to weaken, causing wound secondary dehiscence or bleeding again, endangering patient life and health. Therefore, it is of great significance to develop an injectable hydrogel having both rapid curing and anti-swelling dual performance. Summary of the invention

[0004] In order to solve the technical problems that the curing process of existing injectable hydrogel adhesives is uncontrollable and slow, and most hydrogel adhesives absorb water and expand in the water environment in the body, resulting in decreased adhesion performance and falling off, the present invention aims to provide an injectable hydrogel adhesive and its application with both fast curing and anti-swelling properties.

[0005] The present invention is an injectable hydrogel adhesive with both rapid curing and anti-swelling properties, which is mainly composed of terminal biodegradable poloxamer, adhesion functional small molecules, photoinitiators and dissolving liquids, and is rapidly cured and formed under light conditions. The present invention uses poloxamer nano-micelles with heat-sensitive shrinkage properties as gel factors and cross-linking agents to prepare hydrogels, wherein the heat-sensitive shrinkage nano-micelles enhance the cohesion of the hydrogel and give it anti-swelling properties in a water environment. The photo-induced cross-linking property ensures the rapid and controllable curing of the hydrogel, and the adhesion functional small molecules can be integrated into the hydrogel network during the photo-cross-linking process, providing long-lasting and stable tissue adhesion by covalently bonding with the amino groups on the tissue surface. In addition, the terminal degradable design of the terminal biodegradable poloxamer is used to adjust the degradation time by changing the chemical structure of the poloxamer and the components of the hydrogel, so as to meet the requirements of different degradation times in different usage scenarios.

[0006] The technical solution of the present invention is as follows:

[0007] The first aspect of the present invention provides a terminal biodegradable poloxamer, wherein the terminal biodegradable poloxamer is obtained by introducing terminal modification structures into the two ends of the poloxamer;

[0008] The molecular weight of the terminal modification structure is less than 300, the terminal modification structure contains a biodegradable ester bond or amide bond, and the end of the terminal modification structure is a carbon-carbon double bond;

[0009] The terminal biodegradable poloxamer can be cross-linked by light.

[0010] Furthermore, the chemical structure of the terminal biodegradable poloxamer is shown in Formula I or Formula II below;

[0011] Formula I: n≤10,

[0012] Formula II: R is a side group, and the R side group is an amino acid side group, which is selected according to the side groups of amino acids in the prior art.

[0013] In Formula I and Formula II, x and y are determined according to the type of poloxamer.

[0014] Further, the terminal biodegradable poloxamer is poloxamer diacetyl acrylate, poloxamer dipropionyl acrylate, poloxamer dibutyryl acrylate, poloxamer diglycine acrylate, poloxamer dialanine acrylate or poloxamer diβ-alanine acrylate;

[0015] The chemical structural formula of the poloxamer diacetylacrylate is shown in Formula 1 below;

[0016] The chemical structural formula of the poloxamer dipropionyl acrylate is shown in Formula 2 below;

[0017] The chemical structural formula of the poloxamer dibutyryl acrylate is shown in Formula 3 below;

[0018] The chemical structural formula of the poloxamer diglycine acrylate is shown in Formula 4 below;

[0019] The chemical structural formula of the poloxamer dialanine acrylate is shown in Formula 5 below;

[0020] The chemical structural formula of the poloxamer di-β-alanine acrylate is shown in Formula 6 below;

[0021]

[0022] Furthermore, in the above terminally biodegradable poloxamer, the poloxamer is preferably poloxamer 407, poloxamer 188, poloxamer 237 or poloxamer 338.

[0023] The second aspect of the present invention provides a method for synthesizing terminally biodegradable poloxamer, comprising the following steps:

[0024] The poloxamer is dissolved in dichloromethane, triethylamine and chloroalkyl chloride are added to react, and after the reaction is completed, ether is used for precipitation, and after centrifugation, vacuum drying is performed to obtain poloxamer dichloroalkyl ester; poloxamer dichloroacetate is dissolved in DMF, sodium acrylate is added to react, and after the reaction is completed, ether is added dropwise to precipitate, and after centrifugation, vacuum drying is performed to obtain poloxamer dialkyl acyl acrylate;

[0025] The chemical structural formula of the chloroalkyl acyl chloride is shown in the following formula a, where n≤10;

[0026] Formula a:

[0027] The chemical structural formula of the poloxamer dichloroalkyl ester is shown in the following formula b, where n≤10;

[0028] Formula b:

[0029] The chemical structural formula of the poloxamer dialkyl acyl acrylate is shown in the following formula c, where n≤10;

[0030] Formula c:

[0031] Alternatively, poloxamer is dissolved in toluene, p-toluenesulfonic acid and amino acid are added to react, and after the reaction is completed, ether is used for precipitation, and after centrifugation, vacuum drying is performed to obtain poloxamer diamino acid; poloxamer diglycine is dissolved in dichloromethane, triethylamine and acryloyl chloride are added to react, and after the reaction is completed, ether is added dropwise to precipitate, and after centrifugation, vacuum drying is performed to obtain poloxamer diamino acid acrylate;

[0032] The chemical structural formula of the amino acid is shown in the following formula d, where R is a side group;

[0033] Formula d:

[0034] The chemical structural formula of the poloxamer diamino acid is shown in the following formula e, where R is a side group;

[0035] Formula e:

[0036] The chemical structural formula of the poloxamer diamino acid acrylate is shown in the following formula f, where R is a side group;

[0037] Formula f:

[0038] Furthermore, during the reaction, the molar ratio of the poloxamer to the chloroalkyl acyl chloride, the amino acid, the sodium acrylate and the acryloyl chloride is 1:2.

[0039] The third aspect of the present invention provides use of the terminally biodegradable poloxamer in preparing an injectable hydrogel adhesive.

[0040] The fourth aspect of the present invention provides an injectable hydrogel adhesive having both rapid solidification and anti-swelling properties, wherein the injectable hydrogel comprises the following components in terms of mass percentage:

[0041]

[0042] The adhesion functional small molecules have the ability to react with amino groups and can be integrated into the hydrogel network through light-induced double bond cross-linking;

[0043] The terminally biodegradable poloxamer is selected from one or more of any of the above terminally biodegradable poloxamers.

[0044] Further, the terminal biodegradable poloxamer is selected from one or more of poloxamer 407 diacetyl acrylate (PF127-bis-AA), poloxamer 407 dipropionyl acrylate (PF127-bis-PA), poloxamer 407 dibutyryl acrylate (PF127-bis-BA), poloxamer 407 diglycine acrylate (PF127-bis-GA), poloxamer 407 dialanine acrylate (PF127-bis-AlA) and poloxamer 407 di-β-alanine acrylate (PF127-bis-β-AlA).

[0045] Furthermore, the adhesion functional small molecule is selected from one or more of N-hydroxysuccinimide acrylate (AA-NHS), 3-methacryloyl dopamine (DA-MA) and 4-vinylbenzaldehyde (EBA).

[0046] Further, the photoinitiator is selected from one or more of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone (I2959), 2-hydroxy-2-methyl-1-phenyl-1-propanone (I1173) and phenyl-2,4,6-trimethylbenzoyl lithium phosphite (LAP).

[0047] Furthermore, the dissolving liquid is selected from commonly used medical liquids such as deionized water, physiological saline, PBS buffer or SPF simulated body fluid.

[0048] Furthermore, the components of the injectable hydrogel are cross-linked under 365-405 nm light to form the injectable hydrogel adhesive.

[0049] Furthermore, the injectable hydrogel also contains a natural polysaccharide macromolecular derivative capable of photocrosslinking, and the mass percentage content of the natural polysaccharide macromolecular derivative capable of photocrosslinking is 0.1%-10%.

[0050] Preferably, the photo-crosslinkable natural polysaccharide polymer derivative is selected from one or more of double bond modified gelatin (Gel-MA), double bond modified hyaluronic acid (HA-MA), double bond modified chitosan (CS-MA), double bond modified sodium alginate (SA-MA), double bond modified silk fibroin (SF-MA), double bond modified cellulose (MA-C) and double bond modified glucan (MA-Glu), which can provide the desired biological function.

[0051] The fifth aspect of the present invention provides the use of the injectable hydrogel adhesive with both rapid solidification and anti-swelling properties in sealing and / or rapidly stopping bleeding of accidental trauma or surgical wounds in the human or animal body;

[0052] Preferably, the surgical wound comprises a neurosurgical wound.

[0053] The sixth aspect of the present invention provides an application method of the injectable hydrogel adhesive having both rapid curing and anti-swelling properties, comprising adding the components of the injectable hydrogel adhesive into a dissolving solution to fully dissolve the components, injecting the components into a use site, and inducing a photo-crosslinking reaction after irradiation with a light source, so that the injectable hydrogel is cured;

[0054] Preferably, the wavelength range of the light source is 365-405nm;

[0055] Preferably, the light source irradiates for 5-20 seconds.

[0056] The beneficial effects of the present invention are:

[0057] The injectable hydrogel adhesive provided by the present invention has the ability of rapid photocuring, good biosafety and controllable biodegradation rate, excellent tissue adhesion and mechanical properties, and anti-swelling properties in water environment. When the hydrogel is used clinically, it can quickly seal wounds and stop bleeding, avoid compression damage to surrounding tissues or wound closure failure caused by volume changes after surgery, and can gradually degrade as the wound heals. The injectable hydrogel of the present invention can achieve adhesion to moist tissues within a few seconds after ultraviolet light irradiation, can be used for wound closure and rapid hemostasis, and is particularly suitable for wound treatment in neurosurgery, such as cranial or spinal surgery, to avoid the risk of postoperative adhesive volume expansion compressing neural tissue and ensure the safety of patients after surgery. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 Chemical structures of PF127-bis-AA, PF127-bis-PA, PF127-bis-BA, PF127-bis-GA, PF127-bis-AlA and PF127-bis-β-AlA.

[0059] Figure 2 This is the appearance of an injectable hydrogel adhesive that has both rapid light curing and resistance to swelling.

[0060] Figure 3 The rapid light curing performance of the hydrogel adhesive of the present invention. A: Rheological test of gel time; B: Light curing of hydrogel.

[0061] Figure 4 The anti-swelling property of the hydrogel adhesive of the present invention is compared with the common polyethylene glycol swelling hydrogel. A: Appearance of the hydrogel immersed in PBS at different time points; B: Swelling rate of the hydrogel immersed in PBS at different time points.

[0062] Figure 5The pressure burst tissue adhesion of the hydrogel adhesive of the present invention. A: pressure burst test experimental device; B: pressure burst adhesion data.

[0063] Figure 6 The rapid hemostasis effect of hydrogel adhesive on emergency bleeding in rat and rabbit hearts. (a) Expose the rat heart and create a penetrating bleeding model; (b) Bleeding behavior is demonstrated; (c) Inject the hydrogel adhesive and perform light curing to seal the wound and stop bleeding; (d) Wipe the bleeding site with a clean gauze; (e) There is no blood on the gauze, indicating successful hemostasis. (1) Expose the rabbit heart and create a penetrating bleeding model; (2) Bleeding behavior is demonstrated; (3) Inject the hydrogel adhesive and perform light curing to seal the wound and stop bleeding; (4) Wipe the bleeding site with a clean gauze; (5) There is no blood on the gauze, indicating successful hemostasis.

[0064] Figure 7 The effect of hydrogel adhesive sealing the dura mater injury in rabbits. (1) Exposure of the dura mater; (2) Creation of a dura mater injury model; (3) Successful closure of the dura mater to prevent cerebrospinal fluid leakage. DETAILED DESCRIPTION

[0065] In order to understand the present invention more clearly, the present invention is further described with reference to the following examples and accompanying drawings. The examples are only used for explanation and are not intended to limit the present invention in any way. In the examples, each raw material reagent is commercially available, and the experimental methods without specifying specific conditions are conventional methods and conventional conditions well known in the art, or according to the conditions recommended by the instrument manufacturer.

[0066] Example 1

[0067] Synthesis of PF127-bis-AA, PF127-bis-PA, PF127-bis-BA, PF127-bis-GA, PF127-bis-AlA and PF127-bis-β-AlA:

[0068] 1) Synthesis of terminally biodegradable photo-crosslinked PF127 polymer (PF127-bis-AA):

[0069] Step 1: First, 12.6 g PF127 was dissolved in 100 mL dichloromethane, and then 1 mL triethylamine and 230 mg chloroacetyl chloride were added. After the reaction was completed, the reaction solution was precipitated in ether, collected by centrifugation, and vacuum dried to obtain poloxamer 407 dichloroacetate (PF127-bis-CA).

[0070] Step 2: First, 12.6 g PF127-bis-CA and 190 mg sodium acrylate were dissolved in 50 mL DMF. After the reaction was completed, the reaction solution was added dropwise to ether for precipitation, and then centrifuged and vacuum dried to obtain Loxamer 407 diacetyl acrylate (PF127-bis-AA).

[0071] 2) Synthesis of terminally biodegradable photo-crosslinked PF127 polymer (PF127-bis-PA):

[0072] Step 1: First, 12.6 g PF127 was dissolved in 100 mL dichloromethane, and then 1 mL triethylamine and 250 mg chloropropionyl chloride were added. After the reaction was completed, the reaction solution was precipitated in ether, collected by centrifugation, and vacuum dried to obtain poloxamer 407 dichloropropionate (PF127-bis-CP).

[0073] Step 2: First, 12.6 g PF127-bis-CP and 190 mg sodium acrylate were dissolved in 50 mL DMF. After the reaction was completed, the reaction solution was added dropwise to ether for precipitation, and then centrifuged and vacuum dried to obtain poloxamer 407 dipropionyl acrylate (PF127-bis-PA).

[0074] 3) Synthesis of terminally biodegradable photo-crosslinked PF127 polymer (PF127-bis-BA):

[0075] Step 1: First, 12.6 g PF127 was dissolved in 100 mL dichloromethane, and then 1 mL triethylamine and 280 mg chlorobutyryl chloride were added. After the reaction was completed, the reaction solution was precipitated in ether, collected by centrifugation, and vacuum dried to obtain poloxamer 407 dichlorobutyrate (PF127-bis-CB).

[0076] Step 2: First, 12.6 g PF127-bis-CB and 190 mg sodium acrylate were dissolved in 50 mL DMF. After the reaction was completed, the reaction solution was added dropwise to ether for precipitation, and then centrifuged and vacuum dried to obtain poloxamer 407 dibutyryl acrylate (PF127-bis-BA).

[0077] 4) Synthesis of terminally biodegradable photo-crosslinked PF127 polymer (PF127-bis-GA):

[0078] Step 1: First, 12.6 g PF127 was dissolved in 100 mL toluene, and then 345 mg p-toluenesulfonic acid and 150 mg glycine were added. After the reaction was completed, the reaction solution was precipitated in ether, collected by centrifugation, and vacuum dried to obtain poloxamer 407 diglycine (PF127-bis-Gly).

[0079] Step 2: First, 12.6 g PF127-bis-Gly was dissolved in 100 mL dichloromethane, and then 1 mL triethylamine and 181 mg acryloyl chloride were added. After the reaction was completed, the reaction solution was added dropwise to ether for precipitation, and then centrifuged and vacuum dried to obtain poloxamer 407 diglycine acrylate (PF127-bis-GA).

[0080] 5) Synthesis of terminally biodegradable photo-crosslinked PF127 polymer (PF127-bis-AlA):

[0081] Step 1: First, 12.6 g PF127 was dissolved in 100 mL toluene, and then 345 mg p-toluenesulfonic acid and 180 mg alanine were added. After the reaction was completed, the reaction solution was precipitated in ether, collected by centrifugation, and vacuum dried to obtain poloxamer 407 dialanine (PF127-bis-Ala).

[0082] Step 2: First, 12.6 g PF127-bis-Ala was dissolved in 100 mL dichloromethane, and then 1 mL triethylamine and 181 mg acryloyl chloride were added. After the reaction was completed, the reaction solution was added dropwise to ether for precipitation, and then centrifuged and vacuum dried to obtain poloxamer 407 dialanine acrylate (PF127-bis-AlA).

[0083] 6) Synthesis of terminally biodegradable photo-crosslinked PF127 polymer (PF127-bis-β-AlA):

[0084] Step 1: First, 12.6 g PF127 was dissolved in 100 mL toluene, and then 345 mg p-toluenesulfonic acid and 180 mg β-alanine were added. After the reaction was completed, the reaction solution was precipitated in ether, collected by centrifugation, and vacuum dried to obtain poloxamer 407 diβ-glycine (PF127-bis-β-Ala).

[0085] Step 2: First, 12.6 g PF127-bis-Ala was dissolved in 100 mL dichloromethane, and then 1 mL triethylamine and 181 mg acryloyl chloride were added. After the reaction was completed, the reaction solution was added dropwise to ether for precipitation, and then centrifuged and vacuum dried to obtain poloxamer 407 di-β-alanine acrylate (PF127-bis-β-AlA).

[0086] Example 2

[0087] Preparation of injectable hydrogel with rapid photocuring and anti-swelling properties: First, 100 mg PF127-bis-AA, 1 mg AA-NHS, and 2.5 mg LAP were added to 900 μl PBS buffer and vortexed until fully dissolved; then, the solution was added to a mold and irradiated with 365 nm UV light for 5 seconds to cure the hydrogel.

[0088] Example 3

[0089] Preparation of injectable hydrogel with rapid photocuring and anti-swelling properties: First, 100 mg PF127-bis-AA, 1 mg AA-NHS, 10 mg Gel-MA, and 2.5 mg LAP were added to 890 μl PBS buffer and vortexed until fully dissolved; then, the solution was added to a mold and irradiated with 365 nm light source for 5 seconds to cure to form a hydrogel.

[0090] Example 4

[0091] Preparation of injectable hydrogel with rapid light curing and anti-swelling properties: First, 50 mg PF127-bis-AA, 50 mg PF127-bis-PA, 1 mg DA-MA, and 2.5 mg LAP were added to 900 μl PBS buffer and vortexed until fully dissolved; then, the solution was added to a mold and irradiated with 365 nm light source for 10 seconds to cure to form a hydrogel.

[0092] Example 5

[0093] Preparation of injectable hydrogel with rapid photocuring and anti-swelling properties: First, 50 mg PF127-bis-AA, 50 mg PF127-bis-PA, 1 mg DA-MA, 10 mg HA-MA, and 2.5 mg LAP were added to 890 μl PBS buffer and vortexed until fully dissolved; then, the solution was added to a mold and irradiated with 405 nm light source for 10 seconds to solidify into a hydrogel.

[0094] Example 6

[0095] Preparation of injectable hydrogel with both rapid photocuring and anti-swelling properties: First, add 30 mg PF127-bis-AA, 30 mg PF127-bis-PA, 40 mg PF127-bis-BA, 1 mg EBA, and 2.5 mg LAP into 900 μl PBS buffer and vortex until fully dissolved; then, add the solution into a mold and irradiate with 405 nm light source for 20 seconds to solidify into a hydrogel.

[0096] Example 7

[0097] Preparation of injectable hydrogel with rapid photocuring and anti-swelling properties: First, 30 mg PF127-bis-AA, 30 mg PF127-bis-PA, 40 mg PF127-bis-BA, 1 mg EBA, 10 mg CS-MA, and 2.5 mg LAP were added to 890 μl PBS buffer and vortexed until fully dissolved; then, the solution was added to a mold and irradiated with 365 nm light source for 10 seconds to solidify into a hydrogel.

[0098] Example 8

[0099] Preparation of injectable hydrogel with rapid photocuring and anti-swelling properties: First, 100 mg PF127-bis-GA, 1 mg AA-NHS, and 2.5 mg LAP were added to 900 μl PBS buffer and vortexed until fully dissolved; then, the solution was added to a mold and irradiated with 365 nm UV light for 5 seconds to cure the hydrogel.

[0100] Example 9

[0101] Preparation of injectable hydrogel with rapid light curing and anti-swelling properties: First, 100 mg PF127-bis-GA, 1 mg AA-NHS, 10 mg Gel-MA, and 2.5 mg LAP were added to 890 μl PBS buffer and vortexed until fully dissolved; then, the solution was added to a mold and irradiated with 365 nm light source for 5 seconds to cure to form a hydrogel.

[0102] Example 10

[0103] Preparation of injectable hydrogel with rapid light curing and anti-swelling properties: First, 50 mg PF127-bis-GA, 50 mg PF127-bis-AlA, 1 mg DA-MA, and 2.5 mg LAP were added to 900 μl PBS buffer and vortexed until fully dissolved; then, the solution was added to a mold and irradiated with 365 nm light source for 10 seconds to cure to form a hydrogel.

[0104] Embodiment 11

[0105] Preparation of injectable hydrogel with rapid photocuring and anti-swelling properties: First, 50 mg PF127-bis-GA, 50 mg PF127-bis-AlA, 1 mg DA-MA, 10 mg HA-MA, and 2.5 mg LAP were added to 890 μl PBS buffer and vortexed until fully dissolved; then, the solution was added to a mold and irradiated with 405 nm light source for 10 seconds to solidify into a hydrogel.

[0106] Example 12

[0107] Preparation of injectable hydrogel with rapid photocuring and anti-swelling properties: First, 30 mg PF127-bis-GA, 30 mg PF127-bis-AlA, 40 mg PF127-bis-β-AlA, 1 mg EBA, and 2.5 mg LAP were added to 900 μl PBS buffer and vortexed until fully dissolved; then, the solution was added to a mold and irradiated with 405 nm light source for 20 seconds to solidify into a hydrogel.

[0108] Example 13

[0109] Preparation of injectable hydrogel with rapid photocuring and anti-swelling properties: First, 30 mg PF127-bis-GA, 30 mg PF127-bis-AlA, 40 mg PF127-bis-β-AlA, 1 mg EBA, 10 mg CS-MA, and 2.5 mg LAP were added to 890 μl PBS buffer and vortexed until fully dissolved; then, the solution was added to a mold and irradiated with 365 nm light source for 10 seconds to cure to form a hydrogel.

[0110] The following tests were performed using the hydrogel of Example 3

[0111] 1. Appearance of hydrogel

[0112] The hydrogel is a colorless, highly transparent elastic solid. Figure 2 The left figure is the hydrogel of Example 2, and the right figure is the hydrogel of Example 3. In the process of treating wounds or stopping bleeding, the condition of the wound can be conveniently observed and the treatment plan can be improved in time.

[0113] 2. Gel curing speed

[0114] The photocuring time of the hydrogel was detected by rheological test: the test temperature was 25°C, the hydrogel precursor solution was filled into the test platform (40 mm diameter plate, 1 mm gap), the deformation was 1%, the frequency was 1 Hz, the light source (365 nm, 100 mW cm-2) was set to 0 seconds at the start of irradiation, and the storage modulus (G′) and loss modulus (G″) of the hydrogel were collected over time. The time point when the two intersect is the photocuring time of the hydrogel. The results are shown in the attached Figure 3 A.

[0115] The photocuring efficiency of the hydrogel was tested by weighing method: the hydrogels exposed to different light exposure times were freeze-dried and weighed to obtain the mass Wp. The initial mass Wo of the components in the hydrogel was calculated based on the content of the components in the hydrogel. The ratio of the two is the photocuring efficiency of the hydrogel: Photocuring efficiency % = (Wp / Wo) × 100. The results are shown in the attached Figure 3B. The results show that the gel time of the hydrogel is less than 2 seconds and the complete light curing time is less than 5 seconds.

[0116] 3. Swelling behavior of hydrogel

[0117] The hydrogel was immersed in PBS buffer and maintained at 37°C. The wet weight was measured (Ws) on days 1, 3, and 5, and compared with the initial hydrogel (Wi), the swelling rate was calculated, and its swelling deformation ability was evaluated: swelling rate % = ((Ws-Wi) / Wi) × 100. The polyethylene glycol diacrylate with the same molecular weight was used to replace PF127-bis-AA, and the other components were the same to prepare the polyethylene glycol hydrogel of the control group. The results are shown in the attached Figure 4 The results showed that the hydrogel exhibited excellent anti-swelling behavior within 5 days.

[0118] 4. Tissue Adhesion of Hydrogels

[0119] The tissue adhesion of the hydrogel was tested using a pressure burst experiment. The experimental setup is attached. Figure 5 First, a 2mm diameter hole was made on the surface of the circular pig skin, and then the hydrogel precursor solution was dripped on the wound surface and cured by ultraviolet irradiation for 5 seconds. Finally, the pressure gauge reading when the hydrogel ruptured was observed by injection, that is, the adhesion strength of the hydrogel. The results are shown in the attached Figure 5 . The results show that the burst strength of the hydrogel can reach 200mm Hg, which is much stronger than the human blood pressure of 120mm Hg. It is suitable for rapid hemostasis of emergency bleeding, and the strength does not decrease in the water environment and remains stable. The polyethylene glycol diacrylate with the same molecular weight was used to replace PF127-bis-AA, and the other components were the same to prepare the polyethylene glycol hydrogel in the control group. In contrast, the adhesion strength of the polyethylene glycol hydrogel decreased significantly in the water environment.

[0120] 5. Rapid hemostatic effect of hydrogel

[0121] Using rats and rabbits as model animals, a syringe needle was used to create a puncture injury in the heart to simulate emergency bleeding. Hydrogel adhesive was used to stop bleeding, and the effect is shown in the attached Figure 6 The results showed that injectable hydrogel adhesive can effectively stop bleeding by simply injecting it into the bleeding site and irradiating it with ultraviolet light, and it has the function of quickly stopping bleeding for acute bleeding.

[0122] 6. Application of hydrogels in neurosurgery

[0123] Rabbits were used as model animals to perform spinal surgery to create a dura mater injury model. Hydrogel adhesive was used to seal the dura mater injury to prevent cerebrospinal fluid leakage. The effect is shown in the attached Figure 7The results showed that injectable hydrogel adhesive can be effectively sealed at the site of dura mater injury and then irradiated with ultraviolet light for emergency wound management during neurosurgery.

[0124] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A terminally biodegradable poloxamer, characterized in that: The terminal biodegradable poloxamer is obtained by introducing terminal modification structures into the two ends of the poloxamer; The molecular weight of the terminal modification structure is less than 300, the terminal modification structure contains a biodegradable ester bond or amide bond, and the end of the terminal modification structure is a carbon-carbon double bond; The terminal biodegradable poloxamer can initiate a cross-linking reaction through light irradiation; The chemical structural formula of the terminal biodegradable poloxamer is shown in Formula I or Formula II below; Formula I: n ≤ 10, Formula II: R is a side group, and the R side group is an amino acid side group.

2. The terminally biodegradable poloxamer according to claim 1, characterized in that The terminal biodegradable poloxamer is poloxamer diacetyl acrylate, poloxamer dipropionyl acrylate, poloxamer dibutyryl acrylate, poloxamer diglycine acrylate, poloxamer dialanine acrylate or poloxamer diβ-alanine acrylate; The chemical structural formula of the poloxamer diacetylacrylate is shown in Formula 1 below; The chemical structural formula of the poloxamer dipropionyl acrylate is shown in Formula 2 below; The chemical structural formula of the poloxamer dibutyryl acrylate is shown in Formula 3 below; The chemical structural formula of the poloxamer diglycine acrylate is shown in Formula 4 below; The chemical structural formula of the poloxamer dialanine acrylate is shown in Formula 5 below; The chemical structural formula of the poloxamer di-β-alanine acrylate is shown in Formula 6 below; 3. The terminally biodegradable poloxamer according to claim 2, characterized in that: The poloxamer is poloxamer 407, poloxamer 188, poloxamer 237 or poloxamer 338.

4. A method for synthesizing terminally biodegradable poloxamer, characterized in that: The steps include: The poloxamer is dissolved in dichloromethane, triethylamine and chloroalkyl chloride are added to react, after the reaction is completed, ether is used for precipitation, centrifugation is collected and vacuum drying is performed to obtain poloxamer dichloroalkyl ester; poloxamer dichloroacetate is dissolved in DMF, sodium acrylate is added to react, after the reaction is completed, ether is added dropwise to precipitate, centrifugation is collected and vacuum drying is performed to obtain poloxamer dialkyl acyl acrylate; The chemical structural formula of the chloroalkyl acyl chloride is shown in the following formula a, where n≤10; Formula a: The chemical structural formula of the poloxamer dichloroalkyl ester is shown in the following formula b, where n≤10; Formula b: The chemical structural formula of the poloxamer dialkyl acyl acrylate is shown in the following formula c, where n≤10; Formula c: Alternatively, poloxamer is dissolved in toluene, p-toluenesulfonic acid and amino acid are added to react, after the reaction is completed, ether is used for precipitation, centrifugation is collected and vacuum drying is performed to obtain poloxamer diamino acid; poloxamer diglycine is dissolved in dichloromethane, triethylamine and acryloyl chloride are added to react, after the reaction is completed, ether is added dropwise to precipitate, centrifugation is collected and vacuum drying is performed to obtain poloxamer diamino acid acrylate; The chemical structural formula of the amino acid is shown in the following formula d, where R is a side group; Formula d: The chemical structural formula of the poloxamer diamino acid is shown in the following formula e, where R is a side group; Formula e: The chemical structural formula of the poloxamer diamino acid acrylate is shown in the following formula f, where R is a side group; Formula f:

5. The synthesis method according to claim 4, characterized in that During the reaction, the molar ratio of the poloxamer to the chloroalkyl acyl chloride, the amino acid, the sodium acrylate and the acryloyl chloride is 1:

2.

6. Use of the terminally biodegradable poloxamer according to any one of claims 1 to 3 in the preparation of an injectable hydrogel adhesive.

7. An injectable hydrogel adhesive having both rapid curing and anti-swelling properties, characterized in that: The injectable hydrogel comprises the following components in percentage by mass: The adhesion functional small molecules have the ability to react with amino groups and can be integrated into the hydrogel network through light-induced double bond cross-linking; The terminally biodegradable poloxamer is selected from one or more of the terminally biodegradable poloxamers described in any one of claims 1 to 3.

8. The injectable hydrogel adhesive according to claim 7, characterized in that: The terminal biodegradable poloxamer is selected from one or more of poloxamer 407 diacetyl acrylate, poloxamer 407 dipropionyl acrylate, poloxamer 407 dibutyryl acrylate, poloxamer 407 diglycine acrylate, poloxamer 407 dialanine acrylate and poloxamer 407 diβ-alanine acrylate.

9. The injectable hydrogel adhesive according to claim 7, characterized in that: The adhesion functional small molecule is selected from one or more of N-hydroxysuccinimide acrylate, 3-methacryloyl dopamine and 4-vinyl benzaldehyde.

10. The injectable hydrogel adhesive according to claim 7, characterized in that: The photoinitiator is selected from one or more of 2-hydroxy-4′-(2-hydroxyethoxy)-2-methylpropiophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone and phenyl-2,4,6-trimethylbenzoyl lithium phosphite; The dissolving solution is selected from deionized water, physiological saline, PBS buffer or SPF simulated body fluid.

11. The injectable hydrogel adhesive according to claim 7, characterized in that: The components of the injectable hydrogel are cross-linked under 365-405 nm light to form the injectable hydrogel adhesive.

12. The injectable hydrogel adhesive according to claim 7, characterized in that: The injectable hydrogel also contains a natural polysaccharide macromolecular derivative capable of photocrosslinking, and the mass percentage content of the natural polysaccharide macromolecular derivative capable of photocrosslinking is 0.1%-10%.

13. The injectable hydrogel adhesive according to claim 12, characterized in that The photo-crosslinkable natural polysaccharide polymer derivative is selected from one or more of double bond modified gelatin, double bond modified hyaluronic acid, double bond modified chitosan, double bond modified sodium alginate, double bond modified silk fibroin, double bond modified cellulose and double bond modified dextran.

14. The method for applying the injectable hydrogel adhesive having both rapid solidification and anti-swelling properties according to any one of claims 7 to 13, characterized in that: The components of the injectable hydrogel adhesive are added into a dissolving solution and fully dissolved, and then injected into the use site. After irradiation with a light source, a photo-crosslinking reaction is initiated, so that the injectable hydrogel is solidified.

15. The application method according to claim 14, characterized in that: The wavelength range of the light source is 365-405 nm.

Citation Information

Patent Citations

  • Hydrogel with multiple response function and preparation method and application thereof

    CN107033372A

  • Preparation method of hydrogel with high strength, high water absorption and high transparency

    CN109467655A

  • Injectable hydrogel hemostatic based on marine-derived gelatin as well as application and application method of hemostatic

    CN111632189A

  • Cross-linked poloxamer, cross-linked poloxamerhydrogel and processes for preparing thereof

    KR1020040022575A